Introducing Tax Education in Non-Accounting Curriculum in Higher Education: Survey Evidence - Anis Barieyah Mat Bahari; Lai Ming Ling (Journal of Financial Reporting and Accounting, 2009)
This study aims i) to assess the quest for tax education among working adults that pursuing off-campus non-accounting program, ii) to analyze the level of tax knowledge among the working adults, iii) to elicit the relevant tax topics to be taught should tax education be integrated into non-accounting curriculum in higher education. We surveyed 450 working adults pursuing off-campus non-accounting program in one Malaysian public university. 190 usable responses were received. The survey found 64% of the respondents were keen to learn taxation, and only 23.7% of the respondents possessed high level of tax knowledge. The topics that they desired to learn the most are basic tax principles, personal taxation, tax planning for individuals and taxation for small business and company. The findings suggest that as we moved into the era of self-assessment tax system, it is imperative for the accounting academics and the education authorities to seriously consider introducing tax education in non-accounting curriculum in higher education.
Keywords: H2; 330; Higher education; Malaysia; Non-accounting curriculum; Taxation; Tax education